High-entropy eutectic electrolyte, preparation method thereof and electrochemical device

Through the preparation method of high-entropy low-eutectic electrolyte, the combination of a variety of solvents and diluents and lithium salts is used to solve the problem of insufficient performance of lithium-ion battery electrolytes, achieving efficient lithium ion transfer and extensive electrochemical stability.

CN119812483APending Publication Date: 2025-04-11CENT SOUTH UNIV

Patent Information

Application Number
CN202510005534.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte has problems such as high viscosity, narrow electrochemical stability, flammability, and poor transfer of lithium ion, making it difficult to meet the requirements of high energy density and safety.

Method used

High-entropy low eutectic electrolyte is prepared by mixing lithium salts, multiple solvents and diluents. By adjusting the molar ratio of lithium salts to solvents and the selection of diluents, a local eutectic solvent is formed to improve the performance of the electrolyte.

Benefits of technology

It has achieved the effect of reducing viscosity of the electrolyte, wide electrochemical stability window, low flammability, high transfer number of lithium ions and excellent ion conductivity, and is suitable for various electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812483A_ABST
    Figure CN119812483A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy eutectic electrolyte, a preparation method thereof and an electrochemical device, and the high-entropy eutectic electrolyte is mainly formed by mixing a lithium salt, a solvent and a diluent, the solvent is at least one of sulfone, sulfanilamide, dinitrile and carbonate. The invention further comprises the preparation method of the high-entropy eutectic electrolyte. The electrochemical device comprises a high-entropy eutectic electrolyte, a positive electrode, a negative electrode and a diaphragm. According to the invention, the defects of high viscosity and poor wettability of an aprotic eutectic solvent can be overcome, the diluent is added to form a local eutectic solvent, and the obtained electrolyte has the characteristics of better solubility, low viscosity, wide electrochemical stability, low flammability or inflammability, wide temperature range, high lithium ion transfer number, good ionic conductivity and the like; the method has practical application value in electrochemical devices such as supercapacitors, batteries and sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a high-entropy eutectic electrolyte, a preparation method thereof, and an electrochemical device. Background Art

[0002] With the rapid development of modern society, people's demand for high energy density lithium batteries is also increasing. Lithium-ion batteries are the most successful commercial secondary batteries today. They have advantages such as high actual energy density and long cycle life, so they have attracted widespread attention.

[0003] Electrolyte is an important component of lithium batteries and plays a decisive role in the battery's capacity, life, temperature range, and safety. Therefore, as the requirements for battery performance increase, the optimization of electrolytes has received widespread attention as a powerful means to improve battery performance.

[0004] The electrolyte should have the characteristics of wide operating temperature window, high ionic conductivity, low viscosity, wide electrochemical stability window, non-flammability, and low cost. However, traditional liquid electrolytes cannot meet all of the above requirements. For example: 1) Commercial lithium-ion battery electrolytes are highly flammable; 2) Ionic liquid electrolytes have high viscosity and poor lithium ion transfer numbers; 3) High-concentration electrolytes may have poor low-temperature performance due to salt precipitation. Therefore, the search for new electrolytes suitable for electrochemical devices should continue. In the current public literature, a large amount of highly volatile solvents such as lipids, ketones and ethers are usually used, which is not only unacceptable in cost, but also slightly inferior in safety. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a high-entropy eutectic electrolyte with low viscosity, wide electrochemical stability window, low flammability, high lithium ion transfer number and good ion conductivity.

[0006] The second technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-entropy low-eutectic electrolyte with low viscosity, wide electrochemical stability window, low flammability, high lithium ion transfer number and good ion conductivity.

[0007] The third technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an electrochemical device.

[0008] The technical solution adopted by the present invention to solve the technical problem is that the high entropy eutectic electrolyte of the present invention is mainly composed of a mixture of lithium salt, solvent and diluent.

[0009] The solvent is at least one of sulfone, sulfonamide, dinitrile, carbonate and the like. Preferably, the solvent is at least one of N,N-dimethylmethanesulfonamide, dimethyl sulfone, ethyl methyl sulfone, cyclopentane, malononitrile and succinonitrile. More preferably, two or more solvents are selected. More preferably, 2 to 4 solvents are selected.

[0010] The lithium salt is at least one of bis(trifluoromethylsulfonyl)lithium, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorophosphate, lithium hexafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalate)borate, lithium trifluoromethanesulfonylimide, lithium bis(pentafluoroethanesulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, lithium di(trifluoromethylsulfonyl)imide, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium perchlorate, lithium trifluoropotassium sulfonate, lithium nitrate, lithium carbonate, lithium sulfate, and lithium chloride.

[0011] The diluent is at least one of ether, carbonate, acetamide, nitrile, phosphate, sulfide, sulfoxide, sulfite, sulfone, sulfate, etc. Preferably, the diluent is at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl trifluoromethanesulfonate, and 2,2,2-trifluoroethyl trifluoromethanesulfonate.

[0012] Furthermore, the solubility of the lithium salt in the diluent should be at least 10 times smaller than the solubility of the lithium salt in the solvent, so that the deep eutectic solvent (DES) formed by the solvent and the lithium salt forms a local deep eutectic solvent after the diluent is added, and the solvation structure of the deep eutectic solvent can be maintained.

[0013] Furthermore, the molar ratio of the solvent to the lithium salt is in the range of 0 to 10 to ensure that the lithium salt is fully dissolved. The molar ratio of the diluent to the lithium salt is in the range of 0 to 10.

[0014] Preferably, the molar ratio of the solvent to the lithium salt is controlled to be 2-5. The molar ratio of the diluent to the lithium salt is controlled to be 2-8.

[0015] The method for preparing the high entropy eutectic electrolyte of the present invention comprises the following steps:

[0016] S1. Mixing the lithium salt and the solvent in a certain molar ratio and stirring until a clear and transparent mixed solution is obtained;

[0017] S2. Mix the mixed solution and the diluent in a certain molar ratio and stir to obtain a clear and transparent electrolyte, namely, a high-entropy eutectic electrolyte.

[0018] Preferably, in steps S1 and S2, the stirring temperature is controlled at 30-40°C.

[0019] Furthermore, steps S1 and S2 need to be performed in an argon environment, and both the water content and the oxygen content need to be below 0.2 ppm.

[0020] An electrochemical device comprises the high entropy eutectic electrolyte of the present invention.

[0021] The electrochemical device of the present invention comprises an electrolyte, a positive electrode, a negative electrode and a separator. The electrolyte adopts the high entropy eutectic electrolyte of the present invention.

[0022] The positive electrode is made of at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganate, lithium nickel manganate, lithium cobaltate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, and can also be at least one of sulfur positive electrode, sulfur carbon positive electrode, air positive electrode, etc.; the negative electrode is made of at least one of metal lithium, graphite, silicon negative electrode, silicon carbon negative electrode, silicon oxide and lithium titanate. The diaphragm is made of one of polyethylene, polypropylene, PP / PE / PP three-layer composite film, and glass fiber film.

[0023] The high entropy electrolyte of the present invention comprises a non-proton "deep eutectic solvent (DES)" and a diluent. The solvent and the lithium salt form a deep eutectic solvent (DES). After the diluent is added, a local deep eutectic solvent is formed, which can maintain the solvation structure of the deep eutectic solvent. The electrolyte of the present invention has excellent performance, and has the characteristics of low viscosity, wide electrochemical stability window, low flammability, high lithium ion transfer number, good ionic conductivity, wide temperature range, etc.

[0024] The present invention can solve the shortcomings of high viscosity and poor wettability of aprotic deep eutectic solvent (DES), and a diluent is added to form a local deep eutectic solvent (LDES). The diluent has a poor solvation ability for metal lithium salts, so the microscopic solvation structure of aprotic DES can still be maintained in LDES. Therefore, LDES has both the advantages of DES and overcomes the shortcomings of DES, and is suitable as an advanced electrolyte for electrochemical devices. By studying the influence of high entropy on DES, the electrolyte obtained has better solubility, low viscosity, wide electrochemical stability, low flammability or non-flammability, wide temperature range, high lithium ion transfer number and good ionic conductivity, and has practical application value in electrochemical devices such as supercapacitors, batteries and sensors.

[0025] The present invention is a modification study based on an electrolyte-deep eutectic solvent. The core is the properties between the lithium salt and the solvent. In the deep eutectic solvent, the lithium salt and the solvent are both solid at room temperature. The melting point of the system is reduced by the hydrogen bond structure between the lithium salt and the solvent, making it appear as a liquid phase. The electrolyte in the present invention is not only more cost-effective, but also broadens the selection range of the electrolytic system. The solvent used is non-volatile, less toxic, and safer.

[0026] The local high-concentration electrolyte of the present invention has attracted much attention because it has the advantages of high-concentration electrolyte, low viscosity, high conductivity, etc. The diluent will not destroy the solvation structure of the lithium salt after being added to the electrolyte, and the introduction of the diluent can reduce the concentration of the lithium salt, improve the electrolyte wetting performance, and reduce the electrolyte viscosity, thereby improving the performance of the electrolyte in the battery, and has good commercial application prospects.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] Compared with traditional electrolytes, the high-entropy eutectic electrolyte provided by the present invention has both efficient lithium ion transfer capability and the choice of different types of diluents (high-temperature diluents, low-temperature diluents, etc.), which effectively solves the shortcomings of lithium-ion batteries such as low low-temperature discharge capacity and poor high-temperature safety. At the same time, since the electrolyte system is significantly diversified, the electrolyte of this system has stronger designability, good compatibility with a variety of electrodes, and can better adapt to a variety of battery systems.

[0029] The electrolyte preparation process of the present invention is simple, safer, and has lower cost, and is suitable for industrial production and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The ionic conductivity test results of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2;

[0031] Figure 2 The linear sweep voltammetry curves of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2;

[0032] Figure 3 The coulombic efficiency test results of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2;

[0033] Figure 4 This is the Coulomb efficiency test curve of the electrolyte of Example 1. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments.

[0035] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0036] Example 1

[0037] This embodiment includes the following steps:

[0038] S1. Heat the solvents N,N-dimethylmethanesulfonamide (DMMSA), ethyl methanesulfonate (EMS), and cyclopentane sulfone (TMS) to melt; take 5 mmol DMMSA (0.6159 g), 5 mmol EMS (0.6208 g), 5 mmol TMS (0.6008 g), weigh 5 mmol (0.9354 g) lithium bis(fluorosulfonyl)imide (LiFSI), mix the two and stir at 30°C for 3 hours until a clear mixed solution (LiFSI / DMMSA+EMS+TMS) is formed;

[0039] S2. Take 0.5546 g (1 mmol LiFSI / DMMSA+EMS+TMS, the molar number is based on lithium salt) of the mixed solution obtained in step S1 and mix it with 4 mmol (0.9283 g) 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and stir at 30° C. for 3 hours until a clear and transparent electrolyte is formed, i.e., a high entropy eutectic electrolyte (1 mmol LiFSI / DMMSA+EMS+TMS / 4TTE).

[0040] All the above steps need to be carried out in an argon environment, and the water content and oxygen content need to be below 0.2 ppm.

[0041] Example 2

[0042] This embodiment includes the following steps:

[0043] S1. Heat the solvents N,N-dimethylmethanesulfonamide (DMMSA), ethyl methanesulfonate (EMS), and cyclopentane sulfone (TMS) to melt them; take 5 mmol DMMSA (0.6159 g), 5 mmol EMS (0.6208 g), 5 mmol TMS (0.6008 g), weigh 5 mmol (0.9354 g) lithium bis(fluorosulfonyl)imide (LiFSI), mix the two and stir at 30°C for 2 hours until a clear mixed solution (LiFSI / DMMSA+EMS+TMS) is formed;

[0044] S2, take 0.5546g (1mmol LiFSI / DMMSA+EMS+TMS, the molar number is based on lithium salt) of the mixed solution obtained in step S1, mix it with 2mmol (0.4642g) 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and 2mmol (0.4642g) 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTS), and stir it at 30°C for 2 hours until a clear and transparent electrolyte is formed, i.e., a high entropy eutectic electrolyte (1mmol LiFSI / DMMSA+EMS+TMS / 2TTE+2TTS).

[0045] All the above steps need to be carried out in an argon environment, and the water content and oxygen content need to be below 0.2 ppm.

[0046] Comparative Example 1

[0047] This comparative example comprises the following steps:

[0048] S1. Heat the solvent N,N-dimethylmethanesulfonamide (DMMSA) to melt it; take 15 mmol DMMSA (1.8476 g), weigh 5 mmol (0.9354 g) lithium bis(fluorosulfonyl)imide (LiFSI), mix the two and stir at 30°C for 3 hours until a clear solution (LiFSI / 3DMMSA) is formed;

[0049] S2. Take 0.5566 g of the mixed solution obtained in step S1 and mix it with 4 mmol (0.9283 g) of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and stir it at 30° C. for 3 hours until a uniform solution (1 mmol LiFSI / 3DMMSA / 4TTE) is formed.

[0050] All the above steps need to be carried out in an argon environment, and the water content and oxygen content need to be below 0.2 ppm.

[0051] Comparative Example 2

[0052] This comparative example comprises the following steps:

[0053] S1. Heat the solvent cyclopentane sulfone (TMS) to melt it; take 15 mmol TMS (1.8026 g), weigh 5 mmol (0.9354 g) lithium bis(fluorosulfonyl)imide (LiFSI), mix the two and stir at 30°C for 2 hours until a clear solution (LiFSI / 3TMS) is formed;

[0054] S2. Take 0.5476 g of the solution obtained in step S1 and mix it with 4 mmol (0.9283 g) of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and stir it at 30° C. for 2 hours until a uniform solution (1 mmol LiFSI / 3TMS / 4TTE) is formed.

[0055] All the above steps need to be carried out in an argon environment, and the water content and oxygen content need to be below 0.2 ppm.

[0056] Electrolyte performance test

[0057] Symmetrical steel sheet batteries were assembled, Celgard 2325 was used as the separator, and the electrolyte solutions prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were used as the electrolyte, and the ionic conductivity of the experimental system was measured. The testing principle of ionic conductivity is as shown in Formula III:

[0058]

[0059] In the formula, L is the distance between the symmetrical steel sheets (in cm), which is the thickness of the diaphragm 2.5*10 -3 cm, A is the area of ​​the steel sheet (in cm 2 ), the diameter of the steel sheet is 16.2 mm, so the area A is 2.06 cm 2 ; R b The value of the abscissa corresponding to the intersection of the impedance spectrum and the abscissa in the impedance test (unit: Ω). The calculated result is located at Figure 1 middle, Figure 1 The ionic conductivity test results of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2 are shown below. It is worth noting that the ionic conductivity measured in this way is usually ten times smaller than the actual ionic conductivity due to the influence of the diaphragm. This shows that the battery assembled with the electrolyte obtained by the mixed solvent system of the present invention has relatively excellent ionic conductivity. Figure 1 As shown, by comparing comparative examples 1 and 2 with experimental examples 1 and 2, it can be clearly seen that with the increase in the amount of solvent components, the ionic conductivity of the system is gradually increasing.

[0060] The lithium sheet was used as the negative electrode, the steel sheet was used as the counter electrode, the Celgard 2325 was used as the separator, and the electrolyte solution prepared in Examples 1 and 2 and Comparative Examples 1 and 2 was used as the electrolyte. The electrochemical stability window of the electrolyte was tested at a scan rate of 1 mV / s. The results of the test are listed in Figure 2 , Figure 2 The linear sweep voltammetry curves of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2 show the electrochemical oxidation window of the electrolyte. The oxidation voltage higher than 5.0 V means that the electrolyte of the present invention has a better development space in the field of high-voltage electrolyte. Figure 2 It can also be seen that the stability windows under different components are basically the same, which shows that changing its components has little effect on its electrochemical stability, which lays the foundation for further exploration of the influence of high entropy.

[0061] A lithium-copper pair battery was assembled, with a lithium sheet as the negative electrode, a copper sheet as the positive electrode, Celgard 2325 as the separator, and the solution prepared in Examples 1 and 2 and Comparative Examples 1 and 2 as the electrolyte, and the coulombic efficiency of the experimental system was measured.

[0062] The coulombic efficiency test adopts the average coulombic efficiency method. The specific method is as follows: assemble the lithium copper battery, first plate 5mAh cm on the Cu -2 of Li and stripped to 1 V for one initial cycle, plating 5 mAh cm on Cu -2The Li is used as a lithium reservoir, with a repetitive rate of 1 mAh cm -2 Li stripping / plating, after 9 cycles, all Li is stripped to 1V, calculated as formula (IV):

[0063]

[0064] Q in the formula 循环,剥 , Q 循环,镀 , Q 剥 , Q 镀 , representing the stripping and plating capacity during the cycle, the initial cycle stripping capacity and the plating capacity respectively. The results of the coulombic efficiency determination are located at Figure 3 ; Figure 3 The coulombic efficiency test results of the electrolytes of Examples 1 and 2 and Comparative Examples 1 and 2 are shown. Figure 4 The coulombic efficiency test curve of the electrolyte of Example 1. The coulombic efficiency results show that the battery assembled with the electrolyte obtained by the mixed solvent system of the present invention has a high coulombic efficiency, which means that the battery can maintain a high energy utilization rate after multiple charge and discharge cycles.

Claims

1. A high entropy eutectic electrolyte, characterized in that: It is mainly composed of a mixture of lithium salt, solvent and diluent; The solvent is at least one of sulfone, sulfonamide, dinitrile and carbonate.

2. The high entropy eutectic electrolyte according to claim 1, characterized in that The solvent is at least one of N,N-dimethylmethanesulfonamide, dimethyl sulfone, ethyl methyl sulfone, cyclopentane, malononitrile and succinonitrile.

3. The high entropy eutectic electrolyte according to claim 1 or 2, characterized in that: Two or more solvents are selected.

4. The high entropy eutectic electrolyte according to claim 3, characterized in that Choose 2-4 solvents.

5. The high entropy eutectic electrolyte according to claim 1 or 2, characterized in that: The lithium salt is at least one of bis(trifluoromethylsulfonyl)lithium, bis(fluorosulfonyl)imide lithium, lithium hexafluorophosphate, lithium difluorophosphate, lithium hexafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalate)borate, lithium trifluoromethanesulfonylimide, lithium bis(pentafluoroethanesulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, lithium di(trifluoromethylsulfonyl)imide, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium perchlorate, lithium trifluoropotassium sulfonate, lithium nitrate, lithium carbonate, lithium sulfate, and lithium chloride; and / or, The diluent is at least one of ether, carbonate, acetamide, nitrile, phosphate, sulfide, sulfoxide, sulfite, sulfone, sulfate and the like.

6. The high entropy eutectic electrolyte according to claim 5, characterized in that The diluent is at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl trifluoromethanesulfonate, and 2,2,2-trifluoroethyl trifluoromethanesulfonate.

7. The high entropy eutectic electrolyte according to claim 1 or 2, characterized in that: The solubility of the lithium salt in the diluent should be at least 10 times smaller than the solubility of the lithium salt in the solvent; and / or, the molar ratio of the solvent to the lithium salt is in the range of 0 to 10; and / or, the molar ratio of the diluent to the lithium salt is in the range of 0 to 10.

8. A method for preparing the high entropy eutectic electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Mixing the lithium salt and the solvent in a certain molar ratio and stirring until a clear and transparent mixed solution is obtained; S2. Mix the mixed solution and the diluent in a certain molar ratio and stir to obtain a clear and transparent electrolyte, namely, a high-entropy eutectic electrolyte.

9. The method for preparing a high entropy eutectic electrolyte according to claim 8, characterized in that: In steps S1 and S2, the stirring temperature is controlled at 30-40°C.

10. An electrochemical device, characterized in that: Comprising the high entropy eutectic electrolyte as described in any one of claims 1-7.

Citation Information

Patent Citations

  • Electrolyte for a lithium ion battery

    CN102055018A

  • Lithium ion battery with wide working temperature range

    CN111952670A

  • Electrolyte based on ternary eutectic solvent, preparation method of electrolyte and lithium metal battery

    CN113707938A

  • Electrolyte for lithium battery, lithium battery and method for improving performance of high-temperature lithium battery

    CN114914536A

  • Electrolyte based on sulfuryl eutectic solvent, preparation method of electrolyte and lithium ion battery

    CN115458811A

Cited By

  • Eutectic solvent high-entropy electrolyte and application thereof

    CN120545464A